2008
DOI: 10.1007/s00402-008-0799-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon’s expectations do not predict the outcome of a total knee arthroplasty

Abstract: The outcome of a TKA depends on multiple factors. Both the surgeon's preoperative assessment of the difficulty and the surgeon's immediate postoperative satisfaction do not independently predict the outcome of a TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…It is well accepted that differences exist between patients and surgeons regarding expectations and satisfaction after TKA and hip arthroplasty. 1,2 In a prospective study of 53 primary TKAs, the surgeon preoperatively and immediately assessed the difficulty of the TKA, as well as his or his satisfaction about how well the procedure went. After 1-year follow-up, boththe surgeon's and the patient's satisfaction-were assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well accepted that differences exist between patients and surgeons regarding expectations and satisfaction after TKA and hip arthroplasty. 1,2 In a prospective study of 53 primary TKAs, the surgeon preoperatively and immediately assessed the difficulty of the TKA, as well as his or his satisfaction about how well the procedure went. After 1-year follow-up, boththe surgeon's and the patient's satisfaction-were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established and accepted that patients have different perceptions and expectations compared with their surgeons related to total hip and knee arthroplasty. 1,2 In addition, it has been reported that patients frequently have high and potentially unrealistic expectations for total knee arthroplasty. [3][4][5] Furthermore, patient exposure to media such as the Internet is prevalent and increasing, as is direct to consumer advertising, which may affect the perceptions and expectations they have for pain relief, function, and longevity after TKA.…”
mentioning
confidence: 99%
“…Nine studies 17,21,23,24,32,34,38,40,42 (4070 patients; 2096 preoperative and 2939 postoperative risk estimations) reported surgeons' accuracy in predicting longer-term outcomes, involving patients undergoing orthopaedic 17,32,34,40,42 , general 23,24,38 and neurosurgical 21,40 operations. Outcome measures were heterogeneous and included overall function 21 , pain improvement 23 , global outcome impression 34,40 , hernia recurrence rate 38 , length of hospital stay (LOS) 24 and long-term survival 17 .…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…A number of studies 17,21,34,40,42 found that surgeons significantly and consistently overestimated functional, analgesic and overall satisfaction outcomes after spinal, orthopaedic and neurosurgical operations. A number of studies 17,21,34,40,42 found that surgeons significantly and consistently overestimated functional, analgesic and overall satisfaction outcomes after spinal, orthopaedic and neurosurgical operations.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…However, to the best of our knowledge, this mediation effect is not yet studied. Moreover, numerous studies found that physicians' expectations are not always significantly associated with treatment outcomes [10,15,18,23,24]. For example, physicians generally are worse in predicting outcomes for TKA patients, who in general show less fulfilled expectations, lower improvement rates, longer duration of improvement, and lower level of satisfaction after surgery, than THA patients [15,18,25e31].…”
mentioning
confidence: 99%